SWEDISH AND FINNISH HISTORIOGRAPHIES OF THE SWEDISH REALM, C. 1520-1809. ([S.l.])
1 online resource
Keywords: In the early modern era, two Nordic countries that are neighbours today, Sweden and Finland, formed one realm. Yet, modern history writing has largely ignored this unity, instead developing analysis and discussion in close connection to nationalistic ideas, national politics, and processes of state-building. Historians of both countries have therefore mostly approached their common past separately and academic history in both countries has taken its own course of development, leading to different emphases. This volume explores the common early modern history between Sweden and Finland from the Middle Ages to beginning of the 19th century, and how this history has been created in professional historiography (1860-2020), which methods have been used, and which themes studied. Based on extensive source material, including a database of history publications in different fields in both countries, this book offers a fresh scholarly approach to the study of historiography through a unique comparative perspective. This book is an excellent resource for students and professional researchers alike through providing an alternate view on the history of Sweden and Finland and providing key insight into the historiography of these two countries, and the similarities and differences they showcase.